Is high-volume post-dilution haemodiafiltration associated with risk of fluid volume imbalance? A national multicentre cross-sectional cohort study. Issue 12 (29th August 2019) - Chazot, Charles; Deleuze, Sebastien; Fadel, Baya; Hebibi, Hadia; Jean, Guillaume; Levannier, Martial; Puyoo, Olivier; Attaf, David; Stuard, Stefano; Canaud, Bernard
Abstract: Background: Fluid overload is frequent among hemodialysis (HD) patients. Dialysis therapy itself may favor sodium imbalance from sodium dialysate prescription. As on-line hemodiafiltration (OL-HDF) requires large amounts of dialysate infusion, this technique can expose to fluid accumulation in case of a positive sodium gradient between dialysate and plasma. To evaluate this risk, we have analyzed and compared the fluid status of patients treated with HD or OL-HDF in French NephroCare centers. Method: This is a cross-sectional and retrospective analysis of prevalent dialysis patients. Data were extracted from the EUCLID5 data base. Patients were split in 2 groups (HD and OL-HDF) and compared as whole group or matched patients for fluid status criteria including predialysis relative fluid overload (RelFO%) status from the BCM ® . Results: 2242 patients (age 71 years; female: 39%; vintage: 38 months; Charlson index: 6) were studied. 58% of the cohort were prescribed post-dilution OL-HDF. Comparing the HD and OL-HDF groups, there was no difference between HD and OL-HDF patients regarding the predialysis systolic BP, the interdialytic weight gain, the dialysate-plasma sodium gradient, and the predialysis RelFO%. The stepwise logistic regression did not find dialysis modality (HD or OL-HDF) associated with fluid overload or high predialysis systolic blood pressure. In OL-HDF patients, monthly average convective or weekly infusion volumes per session were not related with the presence of fluid overload. Conclusions: In this cross-sectional study we did not find association between the use of post-dilution OL-HDF and markers of fluid volume excess. Aligned dialysis fluid sodium concentrations to patient predialysis plasma sodium and regular monitoring of fluid volume status by bioimpedance spectroscopy may have been helpful to manage adequately the fluid status in both OL-HDF and HD patients.